Molecular Catalysis Enables Fast Polyiodide Conversion for Exceptionally Long-Life Zinc–Iodine Batteries - Chen, Zihui; Wang, Feifei; Ma, Runlin; Jiao, Wanying; Li, Deyuan; Du, Ao; Yan, Zhijie; Yin, Tianyu; Yin, Xunjie; Li, Qiang; Zhang, Xu; Yang, Nianjun; et al. (ACS energy letters, 2024)
Zinc–iodine (Zn–I2) batteries hold great promise for high-performance, low-cost electrochemical energy storage, but their practical application faces thorny challenges associated with polyiodide shuttling and insufficient cycling stability. Herein, we propose molecular catalysis for long-life Zn–I2 batteries, employing Hemin as an efficient and stable molecular catalyst. The Hemin molecules containing pentacoordinated iron sites significantly adsorb polyiodides, improve the conversion kinetics of iodine species, reduce triiodide concentration, and suppress polyiodide shuttling. Benefiting from molecular catalysis, the Zn–I2 batteries demonstrate an exceptional cycling life, exceeding 62000 cycles with only 0.00052% decay per cycle while maintaining discharge voltage plateaus. The pivotal function of molecular catalysis in both the adsorption and conversion of polyiodide species shows its significant impact on improving the cycling lifespan of Zn–I2 batteries toward long-life energy storage.